Characterization of Teviot virus, an Australian bat-borne paramyxovirus. (28th January 2019) - Johnson, Rebecca I.; Tachedjian, Mary; Clayton, Bronwyn A.; Layton, Rachel; Bergfeld, Jemma; Wang, Lin-Fa; Marsh, Glenn A.
Abstract : Bats are the reservoir hosts for multiple viruses with zoonotic potential, including coronaviruses, paramyxoviruses and filoviruses. Urine collected from Australian pteropid bats was assessed for the presence of paramyxoviruses. One of the viruses isolated was Teviot virus (TevPV), a novel rubulavirus previously isolated from pteropid bat urine throughout the east coast of Australia. Here, we further characterize TevPV through analysis of whole-genome sequencing, growth kinetics, antigenic relatedness and the experimental infection of ferrets and mice. TevPV is phylogenetically and antigenically most closely related to Tioman virus (TioPV). Unlike many other rubulaviruses, cell receptor attachment by TevPV does not appear to be sialic acid-dependent, with the receptor for host cell entry being unknown. The infection of ferrets and mice suggested that TevPV has a low pathogenic potential in mammals. Infected ferrets seroconverted by 10 days post-infection without clinical signs of disease. Furthermore, infected ferrets did not shed virus in any respiratory secretions, suggesting a low risk of onward transmission of TevPV. No productive infection was observed in the mouse infection study.